(untitled) (Al-Mansour Journal, 2026)
The research titled "The Role of Green Libraries and Information Techniques in Enhancing Environmental Awareness in Iraq" explores the significance of green libraries as vital centers for promoting environmental awareness among community members. The study employed a descriptive analytical methodology, collecting data from a sample of 120 respondents. The findings revealed a strong positive correlation between the number of visits to the library and the level of environmental awareness, with a correlation coefficient (r) of 0.95. This indicates that an increase in library visits leads to an increase in environmental awareness by an average of 0.6 points for each additional visit. Furthermore, the study demonstrated that green libraries play a pivotal role in providing information and resources related to environmental issues, thereby contributing to the enhancement of knowledge and interest in environmental matters among individuals. Several factors influencing the effectiveness of libraries in this context were identified, including the availability of educational materials, the quality of programs offered, and community engagement with libraries. In light of the findings, the study recommends the development and implementation of educational programs and workshops in libraries aimed at increasing environmental awareness, with a focus on interactive activities that encourage active participation. It is also advised to strengthen collaboration between libraries and educational and environmental institutions to expand the scope of environmental programs and initiatives. These recommendations aim to enhance the role of green libraries as educational centers that contribute to building an environmentally conscious society, thereby supporting sustainable development in Iraq.